Ways to Organize Extracurricular Activities in Mathematics and Teaching Methodology - Tojiyev Husniddin Baxtiyorovich (Research Parks Publishers, 2021)
This article is about activities that can be out of class and is also useful for students to spend their extracurricular time meaningfully. Today, the world community pays great attention to the efficient use of time. Only those who make useful and good use of their time will grow up to be well-mannered and educated individuals with a worthy place in society.